Effects of urbanization on heavy metal accumulation in surface soils, Beijing - Wang, Meie; Liu, Rui; Chen, Weiping; Peng, Chi; Markert, Bernd (Journal of environmental sciences (China), 2018)
Urbanization processes affect the accumulation of heavy metals in urban soils. Effects of urbanization on heavy metal accumulation in soils were studied using Beijing as an example. It has been suggested that the ecological function of vegetation covers shifting from natural to agricultural settings and then to urban greenbelts could increase the zinc（Zn） concentrations of soils successively. The Zn concentration of urban soils was significantly correlated to the percentage of the impervious land surface at the500 m × 500 m spatial scale. For urban parks, the age or years since the development accounted for 80% of the variances of cadmium（Cd） and Zn in soils. The population density,however, did not affect the heavy metal distributions in urban soils. To conclude, the urban age turned out to be a notable factor in quantifying heavy metal accumulation in urban soils.